Post-Acute Care Interventions in Patients Hospitalized Due to COPD Exacerbation Before and After Implementation of an Integrated Care Program - Hübsch C; Clarenbach CF; Franzen DP; Schmid-Mohler G (International Journal of COPD)
Christine Hübsch,1,2 Christian F Clarenbach,2,3 Daniel P Franzen,2,3 Gabriela Schmid-Mohler1,2 1Centre of Clinical Nursing Science, University Hospital Zurich, Zurich, Switzerland; 2Division of Pulmonology, University Hospital Zurich, Zurich, Switzerland; 3Faculty of Medicine, University of Zurich, Zurich, SwitzerlandCorrespondence: Gabriela Schmid-Mohler, Email gabriela.schmid@usz.chPurpose: In Switzerland, while the quality of acute inpatient care for patients with AECOPD is high, a lack of post-acute care interventions has been identified. To correct this shortfall, an integrated care program for patients with AECOPD was initiated at University Hospital Zurich. The study’s aim was to compare defined post-acute care intervention implementation rates before and after the new program’s implementation.Methods: A retrospective medical chart review was performed regarding patients hospitalized due to AECOPD between July 2019 and March 2023. The control group (CG) had received usual care, while the intervention group (IG) received the newly implemented program. Implementation rates were compared with Pearson’s chi-squared-test or Fisher’s exact test.Results: Charts of 107 participants (IG: 55, CG: 52) were evaluated. Implementation rates increased significantly in the IG for exacerbation management, dyspnea management, recommendation for rehabilitation, smoking cessation advice, evaluation of inhalation technique and recommendation of vaccination (p < 0.05) but not for physical activity, post-discharge medical follow-up or nutrition.Conclusion: This study provides promising evidence that the introduction of a hospital-initiated integrated care program can significantly increase the implementation rate of post-acute care interventions in patients hospitalized due to AECOPD.Keywords: COPD, exacerbation, implementation, post-acute care, nursing